Off-the-Shelf Platform for remote monitoring of vital signs - Barros, Gabriel; Astudillo S., Darwin (Maskana, 2015)
ABSTRACT This document shows work-in-progress in the implementation of a platform for remote monitoring of health care data using ready to use devices. The goal is to provide an easy-to-use application to gather specific control parameters directly related to type 2 Diabetes Mellitus. The idea of remote monitoring for e-health is not new but there exist open questions about the radio technology to use in these applications. Some standards are often associated with these kinds of applications, standards such as: IEEE 802.15.4 and ANT+. We try to explore the benefits of using out of the box technology to reduce development and deployment time of applications sending gathered data over the Internet. The utilization of Smartphones as concentrator node is also discussed, as it make possible to use sensors already embedded in the device as well as other multipurpose and ready to use sensors using ANT+ technology. Keywords: e-health, telemedicine applications, type 2 Diabetes Mellitus, type 2 DM, Remote Monitoring, Android, ANT+. RESUMEN Este documento presenta el trabajo en proceso en la implementación de una plataforma de monitoreo remoto de datos de salud de las personas utilizando dispositivos listos para usar. El objetivo es proveer una aplicación fácil de utilizar para recuperar parámetros de control específicos directamente relacionados con la Diabetes Mellitus de tipo 2. Si bien la idea de monitoreo remoto en el contexto de salud no es nueva, persisten preguntas sobre la tecnología de radio a utilizar en estas aplicaciones. Los estándares frecuentemente relacionados con este problema son: IEEE 802.15.4 y ANT+. Se explotan los beneficios de usar tecnología ya disponible de fábrica para reducir los tiempos de desarrollo y despliegue de aplicaciones que envían datos a Internet. El teléfono inteligente o Smartphone es un nodo concentrador, ya que permite utilizar sensores integrados en el dispositivo, así como otros sensores multipropósito que utilizan la tecnología ANT+. Palabras clave: e-salud, telemedicina, Diabetes Mellitus tipo 2, monitoreo remoto, Android, ANT+.